Analysis Green Economy Based Development Agriculture with Approach Maqashid Sharia Index in Central Tapanuli - Al-Hafidh, Muhammad Najmu; Syahbudi, Muhammad (Trunojoyo University of Madura, 2024)
Development of the agricultural industry and threats environment the more year the more assessed increase from limited amount resident with source power is also limited become felt important for study Already the extent to which the development of the Green Economy is based agriculture with see from corner look maqashid Sharia is in line with draft economy green assessed of 3 indicators maqashid shari’ah index. The aim of this study for know difference performance rather than the green economy of farmers through a number of member from group farmers in the district Central Tapanuli with restrictions study only in sub-districts sorkam namely in groups Serasi Farmers Group, Sepakat Farmers Group, Sakato Farmers Group which is with approach maqashid srai’ah is assessed from Maqashid Sharia Index (MSI). This research was processed using results data observation and interviews. This research uses analysis qualitative descriptive with primary and secondary data collection as well as technical data analysis with approach Maqasid Syariah Index. Result of this research is Performance Assessment of 3 groups farmer that is Serasi Farmers Group, Sepakat Farmers Group, Sakato Farmers Group and the highest are led by Sepakat Farmers Group, more so tall number index show that performance economy matching green with maqashid Sharia Already Enough Good in accordance principle economy green and numbers index group other farmers don’t Far different from Sepakat Farmers Group. This figure can be used as evaluation material for the Central Tapanuli district government and as evaluation material for farmers to care about aspects of the green economy in the agricultural sector and the hope is that it is also in line with the maqashid sharia principle that all aspects of agriculture must comply with the principle of equality.